A new species and new species group of Sweltsa Ricker, 1943 (Plecoptera: Chloroperlidae) - Rehman, Abdur; Huo, Qing-Bo; Du, Yu-Zhou (Zootaxa, 2022)
A new species of the genus Sweltsa Ricker, 1943, Sweltsa lateoblonga Rehman, Du & Huo sp. nov. from Wanglang Nature Reserve, Sichuan Province, China, is described and compared with similar species. A new species group, Sweltsa recurvata group, is proposed for Sweltsa species that lack a transverse ridge on tergum 9. The new species, together with five recognized Palearctic and two Nearctic species, are included in the new group. A taxonomic key to species in this group is included. In addition, unidentified male and female specimens of Sweltsa recorded from Anzihe Nature Reserve, Sichuan Province, and its morphological differences with similar species are discussed with contemporary color images.